Leggso: Financing experimentation - Da Rin, Marco (Journal of Corporate Finance, 2023)
The case is set in Denmark in 2019. It describes the seed funding of Leggso, a cleantech start-up that was developing a new technology for turning lignin (wood scrap) into liquid biofuel. This business clearly had a very large potential upside. The venture, a university spin-off developing within the Danish Cleantech Hub ecosystem, faced several major uncertainties: IP strength, managerial skills, market acceptance, competition. Together with its being a seed stage opportunity, this made investing in the company a riskier choice than usual for Patryk Kyllens, senior investment manager at NORDIA, a VC firm active in the Danish Cleantech Hub ecosystem that had entered negotiations with Leggso. Patryk crafted a syndicated tranched seed round to make the deal appealing to the Supervisory Board of NORDIA. Tranching meant Leggso would now receive a first tranche and would have to satisfy a set of milestones to access the second tranche, twelve months ahead. The deal was signed in April 2018. In March of 2019, Leggso found itself failing one of the milestones. How should Patryk manage this situation? Should he renegotiate and keep investing, or call it a day?